“Biau piring Dayak Iban” the traditional Dayak Iban offering blessing miring poem / Florene Ejot Masanat @ Meramat and Nicholl Ragai Lang - Masanat @ Meramat, Florene Ejot; Ragai Lang, Nicholl (Universiti Teknologi MARA, Kedah, 2024)
Anthology of 200 poems which were contributed by lecturers and academicians from UiTM and other higher learning institutions. This is in fact the largest collection of poems compiled in one anthology.